A window into the abiotic carbon cycle – Acetate and formate in fracture waters in 2.7 billion year-old host rocks of the Canadian Shield. (1st February 2021) - Sherwood Lollar, B.; Heuer, V.B.; McDermott, J.; Tille, S.; Warr, O.; Moran, J.J.; Telling, J.; Hinrichs, K.-U.
Abstract: The recent expansion of studies at hydrothermal submarine vents from investigation of abiotic methane formation to include abiotic production of organics such acetate and formate, and rising interest in processes of abiotic organic synthesis on the ocean-world moons of Saturn and Jupiter, have raised interest in potential Earth analogs for investigation of prebiotic/abiotic processes to an unprecedented level. The deep continental subsurface provides an attractive target to identify analog environments where the influence of abiotic carbon cycling may be investigated, particularly in hydrogeological isolated fracture fluids where the products of chemical water-rock reactions have been less overprinted by the biogeochemical signatures of the planet's surficial water and carbon cycles. Here we report, for the first time, a comprehensive set of concentration measurements and isotopic signatures for acetate and formate, as well as the dissolved inorganic and organic carbon pools, for saline fracture waters naturally flowing 2.4 km below surface in 2.7 billion year-old rocks on the Canadian Shield. These geologically ancient fluids at the Kidd Creek Observatory were the focus of previous investigations of fracture fluid geochemistry, microbiology and noble gas-derived residence times. Here we show the fracture waters of Kidd Creek contain high concentrations of both acetate and formate with concentrations from 1200 to 1900 µmol/L, and 480 to 1000 µmol/L, respectively. Acetate and formate alone account for more than 50–90% of the total DOC – providing a very simple "organic soup". The unusually elevated concentrations and profoundly 13 C-enriched nature of the acetate and formate suggest an important role for abiotic organic synthesis in the deep carbon cycle at this hydrogeologically isolated site. A variety of potential abiotic production reactions are discussed, including a radiolytically driven H, S and C deep cycle that could provide a mechanism for sustaining deep subsurface habitability. Scientific discoveries are beginning to reveal that organic-producing reactions that would have prevailed on Earth before the rise of life, and that may persist today on planets and moons such as Enceladus, Europa and Titan, can be accessed in some specialized geologic settings on Earth that provide valuable natural analog environments for the investigation of abiotic organic chemistry outside the laboratory.